Polymer capsule for self-repairing of inorganic waterproof material and preparation method of polymer capsule
By adding polymer capsules composed of nano Al2O3 and urea formaldehyde resin to the concrete, the water absorption reaction of polyacrylic acid hyperabsorbent resin is used to achieve self-repair of concrete, solving the problem of low efficiency of traditional repair methods and extending the service life of concrete And reduce costs.
Patent Information
- Application Number
- CN202411386999.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional concrete waterproof material repair methods are limited by expensive maintenance costs and crack location and size factors, and the restoration efficiency is not high, making it difficult to effectively extend the service life of concrete.
Polymer capsules for self-healing of inorganic waterproof materials are used. The capsule wall is composed of nano Al2O3 and urea formaldehyde resin. The capsule core is a polyacrylic acid hyperabsorbent resin. By adding these capsules to the concrete, the capsules will burst when the concrete produces microcracks and the inside is The resin reacts with unhydrated cement through water absorption and water release to achieve self-healing.
It significantly improves the restoration rate of concrete, extends its service life, while reducing material costs and production complexity, and improving economic and social benefits.
Smart Images

Figure CN119241121A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of microcapsule material preparation, and specifically relates to a polymer capsule for self-repairing of inorganic waterproof materials and a preparation method thereof. Background Art
[0002] With the increasing amount of infrastructure construction, building resources such as concrete are consumed in large quantities due to their high strength and low cost. However, concrete also has disadvantages such as easy shrinkage in early stage, high brittleness and low tensile strength. When subjected to external stress, micro cracks are easily formed, which then expand into larger cracks. Therefore, it is of great significance to slow down the consumption of concrete and extend its service life.
[0003] Traditional methods for repairing cracks in concrete waterproofing materials include grouting, structural reinforcement, surface treatment, and filling. However, due to the high maintenance costs and the location and size of cracks in actual situations, traditional concrete maintenance and repair methods are difficult to be effectively used. Later, microcapsule repair technology emerged, which is to add microcapsules when mixing concrete. When microcracks appear in concrete, the microcapsules rupture under the stress at the crack tip, and the core material flows out. The core material absorbs and releases water, and the released water reacts with the unhydrated cement in the concrete to self-repair the microcracks. However, the high maintenance costs of traditional inorganic waterproofing materials and the limitations of the location and size of cracks in actual situations make their repair efficiency low. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a polymer capsule for self-repairing of inorganic waterproof materials, and at the same time provide a method for preparing the polymer capsule.
[0005] The technical solution adopted by the present invention is:
[0006] A polymer capsule for self-repair of inorganic waterproof materials, the raw materials used are: 5-40 parts of capsule core material, 30-80 parts of urea, 60-150 parts of formaldehyde solution, 1-8 parts of nano-Al2O3, 0.1-0.5 parts of
[0007] Sodium hydroxide solution, 0.1-0.5 parts of dilute hydrochloric acid solution and 20-80 parts of sodium chloride solution.
[0008] The size of the polymer capsule is 50-150 microns.
[0009] The capsule core material is polyacrylic acid highly absorbent resin.
[0010] The nano Al2O3 is γ-phase nano Al2O3.
[0011] The concentration of the sodium hydroxide solution is 1-2 mol / L.
[0012] The concentration of the dilute hydrochloric acid is 2-4 mol / L.
[0013] The concentration of the sodium chloride solution is 3-5 mol / L.
[0014] The method for preparing a polymer capsule comprises the following steps:
[0015] 1) Weigh each raw material according to the proportion;
[0016] 2) adding sodium chloride solution to the capsule core material and stirring for 1-2 hours to disperse evenly to obtain a solution;
[0017] 3) Mix and dissolve urea and formaldehyde solution, add sodium hydroxide solution to adjust the pH to alkaline (pH 8-9), and stir (50-70° C.) to obtain a formaldehyde-urea prepolymer solution;
[0018] 4) adding the solution obtained in step 2) to the formaldehyde-urea prepolymer solution, adjusting the pH to acidic (pH 2-4) with dilute hydrochloric acid solution, adding nano-Al2O3, and stirring (50-70°C) for solidification;
[0019] 5) Wash the cured capsules twice with deionized water and then dry them to obtain inorganic waterproof material self-repairing polymer capsules.
[0020] In the step 5), the drying is carried out at 50-60° C. for 12-24 hours.
[0021] The stirring speed is 300-1000r / min.
[0022] Compared with the prior art, the beneficial technical effects of the present invention are:
[0023] 1. In the present invention, nano-Al2O3 is added to the capsule wall material of the polymer capsule. Nano-Al2O3 can promote the hydration of C2S and C3S in the cement base to generate CSH gel, and also react with Ca(OH)2 to generate CAH gel, thereby improving the strength of concrete.
[0024] 2. The formaldehyde solution of the present invention reacts with urea under alkaline conditions to form a prepolymer, and then nano-Al2O3 is added under an acidic environment. The prepolymer undergoes a polycondensation reaction and adheres and deposits, thereby forming a capsule wall of urea-formaldehyde resin. Urea-formaldehyde resin is a thermosetting material with high brittleness. When concrete is subjected to temperature stress or external force to produce microcracks, the expanding cracks encounter the capsules. Under the action of the stress at the crack tip, the urea-formaldehyde resin capsule wall is prone to rupture. The polyacrylic acid superabsorbent resin SAP inside the capsule absorbs and releases water, and the water reacts with the unhydrated cement in the concrete to repair the cracks, which can give the concrete inorganic waterproof material the ability to self-repair and extend its service life. The use of the capsule described in the present invention can make the concrete self-repairing and extend the service life of the concrete.
[0025] 3. Adding the polymer capsule of the present invention to concrete waterproof material greatly improves the repair rate of concrete. The material cost used in the preparation is low, the raw materials are easily available, the production process is simple, and it has significant economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram of the structure of the polymer capsule for self-repair of inorganic waterproof material prepared by the present invention.
[0027] Figure 2 This is the appearance of the polymer capsule of Example 1.
[0028] Figure 3 This is the appearance of the product of Example 6.
[0029] Figure 4 The inorganic waterproof material of Example 1 is added to the surface of the test block after pre-compression of the capsule.
[0030] Figure 5 The inorganic waterproof material of Example 1 is mixed into the capsule for pre-compression and continued repair of the test block surface. DETAILED DESCRIPTION
[0031] The specific implementation modes of the present invention are described below in conjunction with examples. However, the following examples are only used to illustrate the present invention in detail and are not intended to limit the scope of the present invention in any way.
[0032] In the following embodiments, nano-Al2O3 is γ-phase nano-Al2O.
[0033] Embodiment 1:
[0034] The raw materials of the self-repairing polymer capsules of inorganic waterproof materials are: 200g polyacrylic acid superabsorbent resin, 500g urea, 900g formaldehyde solution, 40g nano-Al2O3, 3g sodium hydroxide solution (1.5mol / L), 3g dilute hydrochloric acid solution (3mol / L) and 500g sodium chloride solution (4mol / L).
[0035] Embodiment 2:
[0036] The polymer capsules for self-repair of inorganic waterproof materials use the following raw materials: 50g polyacrylic acid superabsorbent resin, 300g urea, 600g formaldehyde solution, 10g nano-Al2O3, 1g sodium hydroxide solution (2mol / L), 1g dilute hydrochloric acid solution (4mol / L) and 200g sodium chloride solution (5mol / L).
[0037] Embodiment 3:
[0038] The polymer capsules for self-repair of inorganic waterproof materials use the following raw materials: 400g polyacrylic acid superabsorbent resin, 300g urea, 1300g formaldehyde solution, 30g nano Al2O3, 4g sodium hydroxide solution (1mol / L), 2g dilute hydrochloric acid solution (2mol / L) and 700g sodium chloride solution (3mol / L).
[0039] Embodiment 4:
[0040] The polymer capsules for self-repair of inorganic waterproof materials use the following raw materials: 150g polyacrylic acid superabsorbent resin, 600g urea, 800g formaldehyde solution, 50g nano Al2O3, 2g sodium hydroxide solution (2mol / L), 4g dilute hydrochloric acid solution (3mol / L) and 400g sodium chloride solution (4mol / L).
[0041] The preparation method of the polymer capsule of Example 1-4 comprises the following steps:
[0042] 1) Weigh each raw material according to the amount;
[0043] 2) adding sodium chloride solution to the polyacrylic acid super absorbent resin, stirring at 600 r / min for 2 h to obtain a uniform solution;
[0044] 3) Mix and dissolve urea and formaldehyde solution, add sodium hydroxide solution to adjust the pH to alkaline (pH 8), and stir at 60° C. and 300-1000 r / min to obtain a formaldehyde-urea prepolymer solution;
[0045] 4) adding the solution obtained in step 2) to the formaldehyde-urea prepolymer solution, adjusting the pH to acidic (pH 3) with a dilute hydrochloric acid solution, adding nano-Al2O3, (60°C), stirring at 300-1000r / min to solidify to obtain capsules;
[0046] 5) The cured capsules are washed twice with deionized water, and then placed in a forced air drying oven and dried at 50-60° C. for 12-24 hours to obtain inorganic waterproof material self-repairing polymer capsules.
[0047] The polymer capsule structures of Examples 1-4 are as follows Figure 1 As shown in the figure, the outer layer is the capsule wall of deposited nano-Al2O3, and the inner core is polyacrylic acid super absorbent resin. Figure 2 As shown, it can be seen that a capsule shape has been formed.
[0048] Embodiment 5:
[0049] The polymer capsules are prepared from the following raw materials: 200 g of polyacrylic acid superabsorbent resin, 500 g of urea, 900 g of formaldehyde solution, 3 g of sodium hydroxide solution (1.5 mol / L), 3 g of dilute hydrochloric acid solution (3 mol / L) and 500 g of sodium chloride solution (4 mol / L).
[0050] Embodiment 6:
[0051] The polymer capsules are prepared from the following raw materials: 200 g of polyacrylic acid superabsorbent resin, 500 g of urea, 40 g of nano-Al2O3, 3 g of sodium hydroxide solution (1.5 mol / L), 3 g of dilute hydrochloric acid solution (3 mol / L) and 500 g of sodium chloride solution (4 mol / L).
[0052] Embodiment 7:
[0053] The polymer capsules are prepared from the following raw materials: 200 g of polyacrylic acid superabsorbent resin, 900 g of formaldehyde solution, 40 g of nano-Al2O3, 3 g of sodium hydroxide solution (1.5 mol / L), 3 g of dilute hydrochloric acid solution (3 mol / L) and 500 g of sodium chloride solution (4 mol / L).
[0054] When preparing Examples 5-7, refer to the method of Examples 1-4.
[0055] Experiments have shown that, due to the lack of formaldehyde or urea, the reaction of Examples 6 and 7 cannot occur, and the capsule wall will not be formed outside the capsule core material super absorbent resin. After drying, the capsule core material super absorbent resin is still in the form of small particles, and finally no capsule is formed. Figure 3 shown.
[0056] The capsule sizes and coverage ratios obtained in Examples 1-5 are shown in Table 1:
[0057]
[0058]
[0059] Application experiment: The polymer capsules obtained in Examples 1-5 were added to concrete respectively, the components were 200g of ordinary Portland cement, 550g of standard sand, 20g of polymer capsules, 5g of polycarboxylate water reducer and 300g of water, and inorganic waterproof material test blocks (size 40mm×40mm×40mm) were prepared. The components of the blank control example were 200g of ordinary Portland cement, 550g of standard sand, 5g of polycarboxylate water reducer and 300g of water, and inorganic waterproof material test blocks (size 40mm×40mm×40mm) were also prepared.
[0060] Each experimental group is divided into the first group, the second group, the third group and the fourth group. The first group has six identical test blocks, the second group has three identical test blocks, the third group has six identical test blocks and the fourth group has six identical test blocks. After curing for 7 days, three test blocks in the first group of each experimental group were subjected to compression test in accordance with GB / T50081-2019, and the average value was calculated to obtain the 7d compressive strength; after curing for 28 days, the other three test blocks were subjected to compression test in accordance with GB / T50081-2019, and the average value was calculated to obtain the 28d compressive strength. After curing for 7 days, the three test blocks in the second group of each experimental group were subjected to pre-compression test to produce cracks. The pre-compression strength was 80% of the 7d compressive strength of the corresponding experimental group. The pre-compression test was continued for 28 days, and the compression test was carried out in accordance with GB / T50081-2019. The average value was calculated to obtain the 28d compressive strength after pre-compression, and the strength recovery rate was calculated according to Eq (1). The results are shown in Table 2.
[0061] Strength recovery rate = 28-day compressive strength after preloading / 28-day compressive strength × 100% Eq (1)
[0062] Table 2 7d and 28d strength (MPa) and strength recovery rate (%) of inorganic waterproof materials
[0063]
[0064] As can be seen from Table 2, the inorganic waterproof material obtained by the present invention has no adverse effect on its compressive strength after being added to the self-repairing polymer capsule. It can be seen that in the blank control group without adding capsules, the 28d strength after pre-compression treatment is improved compared with the 7d strength. This is mainly attributed to the fact that in concrete, with the increase of age, cement will continue to hydrate to produce hydration products to fill cracks and increase strength, but its strength recovery rate is less than 70%. It can be seen from Examples 1-5 that the strength recovery rate of the embodiments with the addition of capsules is greater than 80%, showing better self-repairing performance. In particular, compared with Example 5, Example 1-4 has a higher 28d strength and a better repair effect. In Example 1-4, due to the addition of nano-Al2O3 to the polymer capsule, on the one hand, when the inorganic waterproof material is broken by stress, the polyacrylic acid super absorbent resin in the capsule flows out, absorbs water and expands in the cracks, and fills the cracks; on the other hand, nano-Al2O3 can reduce the nucleation barrier of the concrete hydration product CASH gel, induce its generation, and can participate in the hydration reaction to generate CASH gel and CAH gel. Therefore, the strength recovery rate of Examples 1-4 is greater than that of Example 5, and the repair effect is better.
[0065] Three of the test blocks in the third group of each experimental group were directly cured to 7 days of the test zero period, and the other three test blocks were cured to 28 days of the test zero period, and the anti-seepage test was carried out according to GB / T 50082-2009. The six test blocks in the fourth group were cured to 7 days and pre-compressed, and the pre-compression strength was 80% of the 7-day compressive strength of the corresponding experimental group. Three of the test blocks were subjected to anti-seepage test according to GB / T 50082-2009, and the other three test blocks were further cured for 28 days before the anti-seepage test. The water permeability is shown in Table 3.
[0066] Table 3 Inorganic waterproof material impermeability (%)
[0067]
[0068] Table 3 shows that the blank control example without adding polymer capsules has an improved impermeability after 28 days of pre-pressing and curing, but it is only 28%, which is far from meeting the needs. The inorganic waterproof material prepared after adding the polymer capsules of the present invention has an impermeability rate of more than 82% after continuing to be cured for 28 days after pre-pressing, which is not much different from the impermeability rate when it is not pre-pressed for 28 days. This shows that the cracks generated by pre-pressing after the inorganic waterproof material adds the capsules of the present invention are repaired by the capsules and have good waterproof performance again. Although the cracks are also repaired in Application Example 5, the impermeability rate is only increased to 75%, which is significantly lower than the waterproof performance of Application Examples 1-4. The significant improvement in the impermeability of Examples 1-4 is due to the super absorbent resin in the capsules and the nano Al2O3 on the capsules. The super absorbent resin can respond quickly when the cracks are formed, fill and seal the cracks by absorbing water and swelling, and the nano Al2O3 promotes the generation of more hydration products, making the internal structure of the waterproof material more compact and improving the waterproof performance.
[0069] Example 1: Polymer capsules were added to inorganic waterproof materials and a pre-compression test was performed after curing for 7 days. The surface of the pre-compression test block was as follows: Figure 4 As shown in the figure, the surface of the test block after 28 days of curing is as follows: Figure 5 As shown, it can be seen that the preloading test produced obvious cracks. After 28 days of curing, most of the original cracks have been basically repaired.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. A polymer capsule for self-repair of inorganic waterproof material, characterized in that: The raw materials used are, by weight, 5-40 parts of capsule core material, 30-80 parts of urea, 60-150 parts of formaldehyde solution, 1-8 parts of nano-Al2O3, 0.1-0.5 parts of sodium hydroxide solution, 0.1-0.5 parts of dilute hydrochloric acid solution and 20-80 parts of sodium chloride solution.
2. The polymer capsule according to claim 1, characterized in that: The size of the polymer capsules is 50-150 microns.
3. The polymer capsule according to claim 1 or 2, characterized in that: The capsule core material is polyacrylic acid highly absorbent resin.
4. The polymer capsule according to claim 1 or 2, characterized in that: The nano Al2O3 is γ-phase nano Al2O 3。 5. The polymer capsule according to claim 1 or 2, characterized in that: The concentration of the sodium hydroxide solution is 1-2 mol / L.
6. The polymer capsule according to claim 1 or 2, characterized in that: The concentration of the dilute hydrochloric acid is 2-4 mol / L.
7. The polymer capsule according to claim 1 or 2, characterized in that: The concentration of the sodium chloride solution is 3-5 mol / L.
8. The method for preparing the polymer capsule according to claim 1, characterized in that: The following steps are involved: 1) Weigh each raw material according to the proportion; 2) adding sodium chloride solution to the capsule core material, stirring and dispersing the solution uniformly; 3) mixing and dissolving urea and formaldehyde solution, adding sodium hydroxide solution to adjust the pH to alkaline, and stirring to obtain a formaldehyde-urea prepolymer solution; 4) adding the solution obtained in step 2) to the formaldehyde-urea prepolymer solution, adjusting the pH to acidic with a dilute hydrochloric acid solution, adding nano-Al2O3, and stirring to solidify; 5) Wash the cured capsules twice and then dry them to obtain inorganic waterproof material self-repairing polymer capsules.
9. The preparation method according to claim 8, characterized in that: In the step 5), the drying is carried out at 50-60° C. for 12-24 hours.
10. The preparation method according to claim 8, characterized in that: The stirring speed is 300-1000r / min.
Citation Information
Cited By
Spinel and calcium aluminate multiphase aggregate as well as preparation method and application thereof
CN120329060A
Spinel and calcium aluminate composite aggregate, preparation method and application thereof
CN120329060B
